The Culture of Singapore English - Wong, Jock (Studies in English language, 2014)
"This book provides a fresh approach to Singapore English, by focusing on its cultural connotations. The author, a native Singaporean, explores a range of aspects of this rich variety of English - including address forms, social categories, particles and interjections - and links particular words to particular cultural norms. By using the Natural Semantic Metalanguage (NSM) approach, which is free from technical terminology, he explains the relationship between meaning and culture with maximal clarity, and an added strength of this study lies in its use of authentic examples and pictures, which offer a fascinating glimpse of Singaporean life. Through comparisons with Anglo English, it also explores some difficulties associated with Standard English and cultural misunderstanding. Lending a unique local perspective and written with an incisiveness that makes it ideal for both academic and non-academic readers, this book will appeal to all those interested in Singapore English and its cultural values"--Provided by publisher.